Computational Gastronomy - Use of Computing Methods in Culinary Creativity - Shukla, Durga Prasad; Ailawadi, Pawan (Institut Pariwisata Trisakti, 2019)
Nowadays in culinary practices there is a great variety of regional cuisine in line with the cultural diversity of a place. This raises the question of whether there is a common pattern in determining the combination of food ingredients or the same principles in making recipes and producing certain tastes. For example, Western cuisine tends to use ingredients that have many flavor compounds, while East Asian cuisine tends to avoid ingredients sharing compounds. This study is driven by the results of previous studies showing the science of gastronomy is developing and producing the domain of computational gastronomy which contributes to the creation of recipes in innovative and creative ways. The purpose of this study is to understand the use of computational gastranomy in diverse food network in culinary creativity. The research design is exploring and looking for relationships between various aspects of food such as taste, aroma, seasoning, food ingredient, texture, and cooking methods. Cross sectional and longitudinal research are also carried out to find a causal relationship between computational gastronomy and culinary creation. The results showed that there was a relationship between various aspects, namely computational gastronomy, culinary creations, food content, and the use of technology in creating food recipes. The application of computational creativity in the culinary field can increase business value in the hotel kitchen area, the creation of recipes and food science.